Non Tsinitibo: Games of the Shipibo-Konibo people and its pedagogical use - Gamaniel Monteluisa; Verena Valera; Susana Frisancho; Hans Frech; Enrique Delgado (Pontificia Universidad Católica del Perú, 2015)
In this article we argue that play is a fundamental process for human development, and a necessary tool for the construction of inclusive, intercultural societies. After a brief discussion of the theoretical framework for approaching play as a developmental factor and understanding its relationship with education, we present a collection of Shipibo-Konibo games and some of their possible uses as pedagogical tools. The general intention of this article is to frame play as a developmental process that cannot be ignored if education is to promote interculturality and justice in individuals and societies.